Semantic Access of Relational Databases by mapping Ontology to Relational tables (International Journal of Engineering and Computer Science, 2018)
Ontologies are used as the mediator for different data sources to participate in semantic web. Legacy databases such as the relational and XML based data sources are mapped to Ontologies and are accessed through the SPARQL queries. The proposed method includes the extraction of Ontology from ER/EER diagrams. The conversion of ER/EER diagrams to semantically equivalent Ontologies preserves most of the domain semantics. But in order to make them participate in the semantic web, an efficient method to access these data sources through SPARQL queries should be provided. The  proposed method allows to access the underlying data sources (relational tables)  by executing SPARQL queries on the Ontology extracted from ER/EER schema.